FAKTOR DETERMINAN PENDIDIKAN ISLAM DALAM KAJIAN FILSAFAT - Nur Apriyani; Mahyuddin Mahyuddin (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Education is a system consisting of various interconnected components, such as educational goals, educators, students, the educational environment, and educational tools. The success or failure of education depends not only on schooling but also on the synergy between these factors. This research is a qualitative study using literature review methods to identify the determinants influencing Islamic education, particularly in curriculum development and the formation of students' moral foundations. Each educational system is influenced by a philosophy underlying its educational vision and mission, encompassing views on humans, knowledge, and the ultimate goal of education. This philosophy influences curriculum development oriented toward achieving national educational goals, as well as the development of intellectual, moral, social, and work skills competencies. Furthermore, external factors such as family, environment, media, religion, and educational policy also play a significant role in the formation of students' moral foundations. This research provides insight into the importance of integrating various factors in achieving holistic educational goals. ABSTRAK Pendidikan merupakan sistem yang terdiri dari berbagai komponen yang saling berhubungan, seperti tujuan pendidikan, pendidik, peserta didik, lingkungan pendidikan, dan alat pendidikan. Keberhasilan dan kegagalan pendidikan tidak hanya bergantung pada persekolahan, melainkan pada sinergi antara faktor-faktor tersebut. Penelitian ini merupakan kajian kualitatif yang menggunakan metode studi kepustakaan untuk mengidentifikasi faktor-faktor determinan yang mempengaruhi pendidikan Islam, khususnya dalam pengembangan kurikulum dan pembentukan landasan moral peserta didik. Setiap sistem pendidikan dipengaruhi oleh filosofi yang mendasari visi dan misi pendidikannya, yang mencakup pandangan tentang manusia, pengetahuan, dan tujuan akhir pendidikan. Filosofi ini memengaruhi pengembangan kurikulum yang berorientasi pada pencapaian tujuan pendidikan nasional, serta pembentukan kompetensi intelektual, moral, sosial, dan keterampilan kerja. Selain itu, faktor eksternal seperti keluarga, lingkungan, media, agama, dan kebijakan pendidikan juga memainkan peran penting dalam pembentukan landasan moral peserta didik. Penelitian ini memberikan wawasan tentang pentingnya integrasi berbagai faktor dalam mencapai tujuan pendidikan yang holistik.